Elements of black conservativity in the United States: George Schuyler against civil rights movement (1950-1968) - Francisco, Flavio Thales Ribeiro (Revista de História, 2021)
The aim of this article is to analyze the conservative discourses of the Black intellectual George Schuyler during the period of the Civil Rights Movement. Schuyler was part of a lineage of Black conservatives that had influenced the debate regarding the racial problem in the first half the Twentieth Century, emphasizing moderation and entrepreneurship as a strategy for social development in American capitalism. Schuyler thus moved from the liberal to the right on the political spectrum, vehemently criticizing the strategies of Black leaders such as Martin Luther King Jr, Ella Baker, and Malcom X.